2014
DOI: 10.5152/eajm.2014.23
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Mycobacterium Growth Indicator Tube Method and the Method of Proportion for Drug Susceptibility Testing of Mycobacterium Tuberculosis

Abstract: Objective: Tuberculosis is an important public health problem in developed and, especially, developing countries. The incidence of multidrug-resistant Mycobacterium tuberculosis (MDR-TB) has increased in recent years. Mycobacterial culture and susceptibility testing must be rapidly concluded for effective treatment and control of the disease. The present study evaluated the reliability of the Mycobacterium Growth Indicator Tube (MGIT) method for testing the susceptibility of M. tuberculosis to four first-line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Sub-culturing was performed for 112 LJ-culture positive freezed isolates using BACTEC MGIT 960 instrument (Becton Dickinson, Baltimore, MD, USA) for a maximum of 42 days from initial incubation date.. The drug sensitivity test to streptomycin (S), isoniazid (I), rifampicin (R) and ethambutol (E) was done for all of the successfully recovered sub-culture positive isolates following the protocols [ 14 ]. To control tubes, 0.5 ml of Growth Control working solution was added and labeled as drug free Mycobacterium growth indicator tubes (MGIT), and the other drugs containing tubes were labeled S, I, R and E. The result was interpreted as the growth unit (GU) of the growth control (GC) reached at a minimum value of 400.…”
Section: Methodsmentioning
confidence: 99%
“…Sub-culturing was performed for 112 LJ-culture positive freezed isolates using BACTEC MGIT 960 instrument (Becton Dickinson, Baltimore, MD, USA) for a maximum of 42 days from initial incubation date.. The drug sensitivity test to streptomycin (S), isoniazid (I), rifampicin (R) and ethambutol (E) was done for all of the successfully recovered sub-culture positive isolates following the protocols [ 14 ]. To control tubes, 0.5 ml of Growth Control working solution was added and labeled as drug free Mycobacterium growth indicator tubes (MGIT), and the other drugs containing tubes were labeled S, I, R and E. The result was interpreted as the growth unit (GU) of the growth control (GC) reached at a minimum value of 400.…”
Section: Methodsmentioning
confidence: 99%
“…Each isolate was tested for susceptibility to four first-line anti-tuberculosis agents: isoniazid (0.2 and 0.4 μg/ml), rifampicin (40 and 80 μg/ml), streptomycin (4 and 8 μg/ml) and ethambutol (2 and 4 μg/ml) using Method of Proportion (MOP) on L-J medium [ 12 ]. They all proved susceptible to all tested medicines.…”
Section: Case Presentationmentioning
confidence: 99%
“…[16] In the studies on MDR tuberculosis worldwide, quite different MDR-Mycobacterium tuberculosis complex strain resistance ratios have been reported. In Japan Hattori et al [20] reported a very low ratio of 0.2% in their study; in Indonesia, Lisdawati et al [21] reported MDR-M. tuberculosis complex strain rate as 5.4%, in their study; in Ethiopia, Solomon et al [22] reported a MDR rate of 2.27% in society, while the MDR rate for inmates living in prison was 15.89%; in China, He et al [15] reported a MDR-M. tuberculosis complex strain ratio of 6.2%. In a well-attended study; while in Pakistan Akhtar et al [23] reported a quite high resistance ratio of 69% in their study.…”
Section: Discussionmentioning
confidence: 99%